Rwanda since 1994 : stories of change - Grayson, Hannah; Hitchcott, Nicki (Francophone postcolonial studies ;, 2019)
"Over the past 25 years, Rwanda has undergone remarkable shifts and transitions: culturally, economically, and educationally the country has gone from strength to strength. While much scholarship has understandably been retrospective, seeking to understand, document and commemorate the Genocide against the Tutsi, this volume gathers diverse perspectives on the changing social and cultural fabric of Rwanda since 1994. Rwanda Since 1994 considers the context of these changes, particularly in relation to the ongoing importance of remembering and in wider developments in the Great Lakes and East Africa regions. Equally it explores what stories of change are emerging from Rwanda: creative writing and testimonies, as well as national, regional, and international political narratives. The contributors interrogate which frameworks and narratives might be most useful for understanding different kinds of change, what new directions are emerging, and how Rwanda's trajectory is shaped by other global factors. The international set of contributors includes creative writers, practitioners, activists, and scholars from African studies, history, anthropology, education, international relations, modern languages, law and politics. As well as delving into the shifting dynamics of religion and gender in Rwanda today, the book brings to light the experiences of lesser-discussed groups of people such as the Twa and the children of perpetrators."--